ISWI ATPase Smarca5 Regulates Differentiation of Thymocytes Undergoing β-Selection - Zikmund, Tomas; Kokavec, Juraj; Turkova, Tereza; Savvulidi, Filipp; Paszekova, Helena; Vodenkova, Sona; Sedlacek, Radislav; Skoultchi, Arthur I; Stopka, Tomas (Journal of immunology (Baltimore, Md., 2019)
Development of lymphoid progenitors requires a coordinated regulation of gene expression, DNA replication, and gene rearrangement. Chromatin-remodeling activities directed by SWI/SNF2 superfamily complexes play important roles in these processes. In this study, we used a conditional knockout mouse model to investigate the role of Smarca5, a member of the ISWI subfamily of such complexes, in early lymphocyte development. Smarca5 deficiency results in a developmental block at the DN3 stage of αβ thymocytes and pro-B stage of early B cells at which the rearrangement of Ag receptor loci occurs. It also disturbs the development of committed (CD73+) γδ thymocytes. The αβ thymocyte block is accompanied by massive apoptotic depletion of β-selected double-negative DN3 cells and premitotic arrest of CD4/CD8 double-positive cells. Although Smarca5-deficient αβ T cell precursors that survived apoptosis were able to undergo a successful TCRβ rearrangement, they exhibited a highly abnormal mRNA profile, including the persistent expression of CD44 and CD25 markers characteristic of immature cells. We also observed that the p53 pathway became activated in these cells and that a deficiency of p53 partially rescued the defect in thymus cellularity (in contrast to early B cells) of Smarca5-deficient mice. However, the activation of p53 was not primarily responsible for the thymocyte developmental defects observed in the Smarca5 mutants. Our results indicate that Smarca5 plays a key role in the development of thymocytes undergoing β-selection, γδ thymocytes, and also B cell progenitors by regulating the transcription of early differentiation programs.
Keywords: Chromosomal Proteins, Non-Histone; lymfoidní progenitorové buňky; Mice, Knockout; adenosintrifosfatasy; genová přestavba; receptory antigenů T-buněk alfa-beta; receptory antigenů B-buněk; buněčná diferenciace; Receptors, Antigen, T-Cell, alpha-beta; B-lymfocyty; Lymphoid Progenitor Cells; Thymocytes; Receptors, Antigen, B-Cell; nádorový supresorový protein p53; T-lymfocyty; receptory antigenů T-buněk gama-delta; myši knockoutované; kultivované buňky; Clonal Selection, Antigen-Mediated; klonální selekce zprostředkovaná antigeny; Receptors, Antigen, T-Cell, gamma-delta; Animals; Gene Rearrangement; zvířata; Adenosine Triphosphatases; myši inbrední C57BL; thymocyty; myši; chromozomální proteiny, nehistonové; Mice, Inbred C57BL; B-Lymphocytes; Cells, Cultured; T-Lymphocytes; Mice; Tumor Suppressor Protein p53; Cell Differentiation